An Analysis of Translation Strategies Applied to English Psychological Terms in Indonesian - Felicita Sonya, Anna Maria; Hastuti, Erni (International Journal of English and Applied Linguistics (IJEAL), 2026)
This study aims to identify how strategies of translation were applied in English psychological terms that translated into Indonesian. Certain terms may be too specific or too general; it can cause challenges to the translator itself. However, translators must consider a proper way to transfer the meaning culturally and linguistically relevant to the target text. Through this study, it will focus on describing the detailed process of transferring meaning from the source text to the target text to obtain factual data and information related to the translation strategies used by the translator. Therefore, qualitative methods were applied in this study. A total of 28 data were gathered from the book by Viktor E. Frankl entitled Man’s Search for Meaning. The data are words and phrases that belong to psychological terms, then data were analyzed using Andrew Chesterman translation strategies. Chesterman’s strategies are divided into three main groups as well as syntactic strategy, semantic strategy and pragmatic strategy. Each group represents different levels of linguistic unit. Then the result shows that from all the data that have been collected, 6 out of 30 strategies are applied in the translation, that is literal translation 7 data, loan 1 data, calque 11 data, unit shift 3 data, paraphrase 4 data and cultural filtering (adaptation) 4 data.